Cultural adaptation of an intervention to prevent postnatal depression and anxiety in Chilean new mothers. (27th May 2021) - Coo, Soledad; García, María Ignacia; Awad, Natalia; Rowe, Heather; Fisher, Jane
ABSTRACT: Objective : The aim of this study was to culturally adapt What Were We Thinking (WWWT), an Australian psychoeducational intervention to prevent symptoms of depression and anxiety among first-time mothers, to be used in the Chilean primary health system. Background : Mental health symptoms are common in first-time mothers. Despite the availability of effective screening and referral in the Chilean primary health system, very few women access treatment due to diverse barriers. This highlights the importance of using a preventive approach. The evidence that culturally-adapted, evidence-based preventive programmes can reduce maternal mental health problems supports the development of this study. Methods : WWWT materials were translated into Spanish. Cultural Adaptation and field testing were conducted following the Cultural Adaptation Model. Results : Modifications to the intervention included adding an explicit infant mental health approach, a simplification of written information, and changes in the number and duration of the sessions. The adapted version of WWWT was considered understandable and relevant for local perinatal mental health specialists, new mothers and their partners. Conclusion : The Spanish version of WWWTis a culturally sensitive intervention, its potential for effective use in the Chilean context warrants further investigation. Limitations and implications for future studies are discussed.